2008
DOI: 10.2214/ajr.07.3281
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Mixed Müllerian Tumor of the Uterus: Findings on Sonography, CT, and Gadolinium-Enhanced MRI

Abstract: Uterine MMMT most commonly presents as an intracavitary mass with coexistent dilatation of the endometrial canal. Tumors tend to appear hyperechoic on sonography, heterogeneously hypodense and ill defined on contrast-enhanced CT, and heterogeneously hyperintense on T2-weighted MR images with signal abnormalities indicating subacute hemorrhage on T1-weighted MR images. Myometrial invasion is common and has a predilection for the uterine fundus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 15 publications
3
30
3
1
Order By: Relevance
“…**Contrast-enhanced T 1 -weighted image was not obtained for one case. CER, contrast-enhanced ratio of main solid part; n. s., not significant; SI, signal intensity intensity on T 2 -weighted images, 16,18,19 but they have been reported to have no specific MR findings because of various coexisting malignant components that include necroses and hemorrhages. In particular, small-sized carcinosarcomas are difficult to distinguish from endometrial carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…**Contrast-enhanced T 1 -weighted image was not obtained for one case. CER, contrast-enhanced ratio of main solid part; n. s., not significant; SI, signal intensity intensity on T 2 -weighted images, 16,18,19 but they have been reported to have no specific MR findings because of various coexisting malignant components that include necroses and hemorrhages. In particular, small-sized carcinosarcomas are difficult to distinguish from endometrial carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…MMMT texture on T2-weighted images was heterogenous in 82%. In the study by Teo et al (6), two MMMTs showed intense, but heterogenous enhancement after gadolinium administration; whereas, 80% of patients in the study by Tanaka et al (7) showed area of avid enhancement.…”
Section: Index Termsmentioning
confidence: 89%
“…The number of CT annual examinations per 1000 people in Japan was the 6th among 17 countries (146 vs. a mean of 122), and that of MR examinations was the 4th (68 vs. a mean of 45). Japan belongs to the group with a high number of examinations, but the number is not impressive, considering the very high number of systems (Fig.…”
Section: Comparisons Between Japan and Foreign Countriesmentioning
confidence: 97%
“…Endometrial stromal sarcoma exhibits various invasion patterns, and MRI findings such as bands of low signal intensity on T2-weighted imaging and continuous tumor extent along the blood vessels and the ligaments are informative [121]. Carcinosarcoma is difficult to differentiate from uterine body cancer; however, on MRI it is a large mass that dilates the uterine cavity and shows characteristic MRI features such as heterogeneous hyperintensity on T2-weighted imaging, early and persistent enhancement and/or gradual and delayed strong enhancement [122,123].…”
Section: Commentsmentioning
confidence: 99%